Citizen Charter As An Innovation In Publik Service Management - Mudassir Mudassir; Rifdan Rifdan (Program Pascasarjana Universitas Negeri Makassar, 2023)
Tracing the problems of public services in Indonesia can actually be seen in several periods of governance, for example starting during the New Order era and finally the reform period. The citizen charter service contract is one of the innovations in public service management towards responsive service delivery and in accordance with the needs of the community. In the citizen charter service contract requires active involvement of citizens, also empowering citizens through the introduction of rights and obligations between users and service providers which will raise citizen awareness to control the implementation of public services. citizens also have the right to participate in the delivery of services and citizens must also be empowered so that they have a bargaining position when dealing directly with the service provider bureaucracy. The implementation of the citizen charter service itself consists of five principles, namely service vision and mission, service standards, service flow, community complaint unit, service user survey